A colorimetric chemosensor for sulfide in a near-perfect aqueous solution: practical application using a test kit. Issue 88 (7th September 2016) - Lee, Seong Youl; Kim, Cheal
Abstract : A selective chemosensor with practical applications was developed for the colorimetric detection of S 2− in a near-perfect aqueous solution. Abstract : A new highly selective colorimetric chemosensor1 N ′1-(( E )-2, 3-dihydroxybenzylidene)- N ′2-(( Z )-2, 3-dihydroxybenzylidene)oxalohydrazide for S 2− was designed and synthesized. The sensor1 showed a selective colorimetric sensing ability toward S 2− by changing color from colorless to yellow in a near-perfect aqueous solution. To understand the sensing mechanism of1 with S 2−, UV-vis spectroscopy, ESI-mass spectroscopy analysis and DFT calculations were carried out. Practically, sensor1 functioned as a visible test strip for S 2− . Moreover, the sensing ability of1 for S 2− was successfully applied in real water samples. Therefore, sensor1 could be a good alternative method for onsite and real time screening of S 2− .